Estudo numérico do comportamento de muros de arrimo em alvenaria estrutural de blocos vazados - Santos Júnior, Gilvan Bezerra dos (2014)
Usually masonry structures has low tension strength, hence the design to flexural efforts can results in high reinforcement ratio, specification of high unit and prism strength, structural members with larger section dimensions and modification in structural arrangement to be possible to use masonry members. The main objective of this study is to evaluate the stiffness, the efforts distribution and the effect of horizontal elements (girders) and vertical elements (counterforts) distribution on the behavior of masonry blocks retaining walls. For this purpose, numerical modeling was performed on typical retaining wall arrangements by varying the amount and placement of horizontal and vertical elements, beyond includes elements simulating the reactions of the soil supporting the foundation of the wall. The numerical modeling also include the macro modeling strategy in which the units, mortar and grout are discretized by a standard volume that represents the masonry elastic behavior. Also, numerical model results were compared with those ones of simplified models usually adopted in bending design of masonry elements. The results show horizontal displacements, principal and shear stresses distribution, and bending moments diagrams. From the analysis it was concluded that quantity and manner of distribution of the girders are both important factors to the panel flexural behavior, the inclusion of the foundation changed significantly the behavior of the wall, especially the horizontal displacements, and has been proposed a new way of considering the flanges section of the counterforts